The relationship between chronotype preferences and academic achievement among university students at faculty of technology management and business UTHM, Johor [electronic resource] - 634336 Nor Hidayah Shamsuri, 1992- author (Skudai: Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Psikologi dengan Pembangunan Sumber Manusia)) - Universiti Teknologi Malaysia, 2017